Rumusan Terminologi Keamanan Maritim Dipandang dari Sisi Partisipasi Masyarakat - Pratondo Ario Seno; Firdaus, Elsa Aliya Rizqoh (Veteran Law Review, 2024)
There has not been a single concept about maritime security that caused plurality in giving the multi-aspect meaning of maritime security, meanwhile the necessary of maritime security law demands the necessary of a single concept about maritime security. Terminology of maritime security is necessary to arrange master plan in reaching national objective in maritime sector that decided by President Joko Widodo as maritime global fulcrum vision. This research aims to formulate terminology of maritime security by using people participation’s point of view or with the other word to formulate meaning of maritime security participatory. The methods used in this research are qualitative method, normative law method, and legal system method with the result is terminology of maritime security formulated as “realization of people participation by checks and balances principle to uphold law state supremacy in sea region to reach global maritime fulcrum”.